2002
DOI: 10.1021/ma010192y
|View full text |Cite
|
Sign up to set email alerts
|

Dewetting of Thin Diblock Copolymer Films:  Spinodal Dewetting Kinetics

Abstract: The stability of thin diblock copolymer films with respect to the annealing above the microphase separation temperature is investigated on long time scales and at different film thicknesses. Poly(styrene-block-p-methylstyrene) diblock copolymer films on top of silicon substrates are examined with scanning force microscopy and off-specular X-ray scattering. At film thickness below the lamellar spacing of the bulk material a dewetting is observed. The kinetics of the film destabilization are explainable within a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
48
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 54 publications
(134 reference statements)
4
48
0
Order By: Relevance
“…To investigate the correlation of the dewetted holes along the film surface, fast Fourier transition (FFT) was performed by taking There is a peak at q = 0.0044 nm −1 , corresponding to the periodic structures with size of 1400 nm. The result makes it clear that the holes are correlated with each other, which is a typical symbol of spinodal dewetting or dewetting by means of composition fluctuation [27][28][29].…”
Section: Resultsmentioning
confidence: 92%
“…To investigate the correlation of the dewetted holes along the film surface, fast Fourier transition (FFT) was performed by taking There is a peak at q = 0.0044 nm −1 , corresponding to the periodic structures with size of 1400 nm. The result makes it clear that the holes are correlated with each other, which is a typical symbol of spinodal dewetting or dewetting by means of composition fluctuation [27][28][29].…”
Section: Resultsmentioning
confidence: 92%
“…In many previous studies, the film instability of diblock copolymers has been investigated in disordered state above the ODT temperature . Recently, several studies reported hierarchical patterns formed as a result of dewetting and microphase separation in diblock copolymer thin films.…”
Section: Discussionmentioning
confidence: 99%
“…Little is understood about the film instability and dewetting of copolymer liquids . Despite experiments and theories on these instabilities, there remain discrepancies in the morphology and dynamics of dewetting between BCP liquids and simple polymer liquids.…”
Section: Introductionmentioning
confidence: 99%